A thermodynamic view of heat transfer in different transport regimes - Schubler, Gulru Babac (Author(s), 2016)
The nature of the heat transfer process changes substantially according to transport regime. A thermodynamic view to micro/nano scale flows is considered to get a better understanding within this regime dependent change. The transport processes are expressed as a polytropic process and T-s diagram of different transport regimes are presented. In addition, a molecular dynamic simulation of nano channel flows is presented. Since the polytropic processes are strongly related with the heat capacities, the heat capacity calculations are also taken into account in MD simulations. The theoretical predictions are approved with the molecular dynamic simulations for monatomic gases.